EFFECTS OF AGROCHEMICALS AND THEIR IMPACT ON SOIL QUALITY IN PART OF SUDAN SAVANNAH ZONE OF NORTHWESTERN NIGERIA - Hassan, Isah Usman; Garba, Yusuf Idris; Hussain, Ahmad (FUDMA JOURNAL OF SCIENCES, 2025)
The use of agrochemicals causes a number of environmental issues, including harm to human health, contamination of groundwater and other aquatic habitats, and soil degradation that lowers soil quality and turns many formerly productive agricultural lands into unproductive ones. This study assessed the effect of agrochemicals on soil quality in the area. A survey was conducted among 331 farmers from seven villages in Bunkure Local Government Area Kano State. Soil samples were also collected and analyzed to determine various soil parameters (OC, P, N, CEC, Ca2+, Na2+, Mg2+ and K2+). Questionnaire was used to obtain information on the farmers knowledge and perception regarding agrochemical application and impact to soil quality. The results revealed that a majority (78%) of the farmers had been using agrochemicals for more than four years, with most (76%) applying those more than twice per year. Furthermore, a significant proportion (61%) indicated awareness of the impact of agrochemicals on soil quality. In addition, findings indicated that 94% of the respondents believed that the use of agrochemicals affected soil quality. Among them, 83% reported a positive effect on soil quality, while 10% observed a negative effect. Only 4% perceived no effect of agrochemicals on soil quality. The amount of Organic Carbon, Phosphate, Nitrogen, and Cation Exchange Capacity (CEC) were found to be within the permissible limits set by the World Health Organization (WHO) with exception of phosphate. Additionally, the cation distribution in the soil profile followed the order: Ca2+ > Na2+ > Mg2+ > K2+. The average concentrations...
Keywords: Soil quality; Agrochemicals application; Farmers knowledge; Kano state